ANALISIS PENGARUH PERBANKAN SYARIAH TERHADAP PERTUMBUHAN SEKTOR RIIL DI INDONESIA - Fadil Ananta Piskha; Hasdi Aimon; Mike Triani (Universitas Negeri Padang, 2018)
The purpose of this study is to see the effect of Islamic Banking on the growth of real sector in Indonesia. The type of data in this research is time series. In analyzing sequential data from 2007 and 2017, the analytical method is used OLS analysis methods. Based on the results of estimation, financing, third party funds and certificates of Indonesian Islamic banks have significant influence on the growth of the real sector. Sharia Indonesia bank financing and certificates have a positive effect on real growth sector. Islamic banking encourages the growth of the real sector in terms of financing in the distribution of capital, certificates of Indonesian Islamic banks instruments encouraging real sector movements and supporting the large amount of capital to be distributed While third party funds have a negative effect on real growth sector.